2019
DOI: 10.1002/cncr.32590
|View full text |Cite
|
Sign up to set email alerts
|

Light to moderate amount of lifetime alcohol consumption and risk of cancer in Japan

Abstract: Background Even light to moderate alcohol consumption has been shown to increase cancer incidence. However, this association has not been well characterized in Japan. Methods Based on a nationwide, hospital‐based data set (2005‐2016), a multicenter case‐control study was conducted (63,232 cancer cases and 63,232 controls matched for sex, age, admission date, and admitting hospital). The total amount of lifetime alcohol consumption (drink‐years) was recalled for each patient by multiplication of the daily amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 34 publications
(195 reference statements)
0
34
0
3
Order By: Relevance
“…Liver and intrahepatic bile duct malignancies are a leading cause of death worldwide, and hepatocellular carcinoma (HCC) is a representative malignancy among liver cancers 32 . The most common causes of liver cancer are lifestyle factors such as alcohol drinking (even moderate) and hepatitis B and C viral infections [32][33][34] . Chronic inflammation and oxidative stress are major intermediate aetiologies bridging environmental risk factors and carcinogenesis 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Liver and intrahepatic bile duct malignancies are a leading cause of death worldwide, and hepatocellular carcinoma (HCC) is a representative malignancy among liver cancers 32 . The most common causes of liver cancer are lifestyle factors such as alcohol drinking (even moderate) and hepatitis B and C viral infections [32][33][34] . Chronic inflammation and oxidative stress are major intermediate aetiologies bridging environmental risk factors and carcinogenesis 33 .…”
Section: Discussionmentioning
confidence: 99%
“…A study from Japan, which is another country with a high prevalence of ALDH2*2 allele carriers, reported that even light to moderate level of drinking was associated with an increased risk of cancer (OR for 10 drink‐years = 1.05; 95% CI, 1.04‐1.06 compared to never drinkers) 27 . In addition, those who drank 2 or fewer drinks per day had an increased cancer risk regardless of the drinking duration 27 . Our results further indicated that, among those genetically susceptible to the carcinogenic effect of alcohol, lower educational levels further enhanced the risk of alcohol‐related HNC.…”
Section: Discussionmentioning
confidence: 99%
“…The rs2236316 polymorphism was not included in the breast cancer study. Cigarette smoking and alcohol consumption have been suggested to influence the risk of CRC development in epidemiological studies (2)(3)(4)(5)(6). In a pooled meta-analysis based on cohort and case-control studies, smoking was not shown to significantly increase the risk of CRC in Japanese individuals (2), whereas, alcohol consumption was reported to have a more significant positive association with the risk of CRC in the Japanese than those in Western populations (7).…”
Section: Discussionmentioning
confidence: 99%
“…At present, the implementation of CRC population screening has contributed to the reduction of morbidity and mortality rates, which indicates that the earlier the CRC diagnosis is confirmed, the more effective and easier the therapeutic treatment to patients will be, resulting in favorable prognoses. Among the different epidemiological factors, cigarette smoking and alcohol consumption have been known to be associated with a higher risk of CRC (2)(3)(4)(5)(6). In particular, alcohol consumption shows a significantly higher association with CRC in Japanese individuals compared with Western populations (7).…”
Section: Introductionmentioning
confidence: 99%